Clinical characteristics in patients with coronary slow flow phenomenon: A retrospective study. Issue 6 (12th February 2021) - Huang, Qiaojuan; Zhang, Fan; Chen, Siyu; Dong, Zhaoying; Liu, Weiwei; Zhou, Xiaoli
Abstract : Abstract: Coronary slow flow phenomenon (CSFP) is a coronary artery disease in which coronary angiography shows no obvious stenosis, but there is a delay in blood flow perfusion. The etiopathogenic mechanisms of CSFP are still unclear. The aim of the present study was to investigate the role of clinical characteristics in patients with CSFP, and to provide a reference for exploring the potential mechanisms of CSFP. Patients with angiographically normal epicardial arteries were enrolled (145 patients with CSFP and 145 normal controls). Collected clinical information and laboratory indexes, which measured by peripheral venous blood samples before coronary angiography. Logistic regression analysis was performed for statistical analysis. The present study found 19 clinical and laboratory indexes with statistical differences between the two groups in univariate analysis. Multivariate analysis showed that monocyte count, haemoglobin, serum creatinine and globulin were independent predictors of CSFP. Moreover, the monocyte count, haemoglobin, creatinine and globulin levels were significantly higher in the CSFP patients than the controls, with positive associations between these parameters and the extent of CSFP. In addition, ROC analysis showed the diagnostic value of the above indexes for CSFP.